Rural-urban difference in blood pressure measurement frequency among elderly with hypertension: a cross-sectional study in Shandong, China - Qian Wang; Lingzhong Xu; Long Sun; Jiajia Li; Wenzhe Qin; Gan Ding; Jiao Zhang; Jing Zhu; Su Xie; Zihang Yu; Chengchao Zhou (BMC, 2018)
Abstract Background Blood pressure measurement is the first step in preventing and controlling hypertension. The objective of this study is to examine the rural-urban difference towards blood pressure measurement among elderly with hypertension. Methods A total of 2007 elderly (65+) were selected from the fifth Health Service Survey of Shandong Province in 2013. A standardized questionnaire was used to investigate the demographic characters, socioeconomic status, self-rated health, and blood pressure related index. Three logistic regression models were used to examine the difference in blood pressure measurement between rural and urban elderly. Unadjusted and adjusted logistic regression models were used to explore the associated factors of blood pressure measurement in both rural areas and urban areas. Results The prevalence of weekly blood pressure measurement in urban elderly was higher than that in rural elderly (63.9% vs 34.3%). The rural elderly had an odds ratio (OR) for weekly blood pressure measurement of 0.467 (95%CI = 0.380-0.575) compared with urban elderly. Binary logistic regression analysis showed that medication frequency and accepting health care professionals' guidance were common associated factors of blood pressure measurement among both rural and urban elderly; personal income was unique associated factor of blood pressure measurement among rural elderly; marital status, education level, self-rated health, and blood pressure level currently were unique associated factors of blood pressure measurement among urban elderly. Conclusions There is a big difference in blood pressure measurement between rural and urban elderly. Interventions targeting identified at-risk subgroups, especially for those rural elderly, should be made to reduce such a gap.